On the Process of Liberation of the Baltic Countries from the Soviet Domination in Years 1985-1991: Attempt at a Model - Brzechczyn, Krzysztof (Wyższa Szkoła Finansów i Zarządzania w Białymstoku, 2008)
The aim of this paper is to analyze the beginnings and growth of civil movements in the Baltic republics in years 1985-1991, which led to their state independence. Proces of liberation of Baltic societies will be analyzed according to the following criteria: size and range of the civil movement and forms of its institutionalization (i), political concession made by republican authorities (ii) and level of control over the republican structure of power exercised by the civil movements (iii). Finally, I will try to consider why evolution of the Baltic societies resulted in building of the stable democracies, whereas these same efforts are still unsuccesful in Belarus and were unsuccesful in Ukraine. This analysis will not be a chronicle's presentation of events from current history of the Baltic states but will be based on a coherent theoretical framework achieved by employing models and conceptual apparatus of non-Marxian historical materialism.
Keywords: Lithuania; Latvia; Estonia; Baltic states; Non-Marxian historical materialism; Soviet Union; Decline of communism; Soviet empire